Performance Characteristics of Six-Phase Induction Generator for Renewable Power Generation - Alok Kumar Mohanty; K B Yadav (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper presents the performance behavior of a multi-phase induction generator operating in six-phase mode. An experimental analysis has been done to determine operating characteristics of the six-phase machine to illustrate the advantageous features of the machine as compared to its three phase counterpart. The machine is configured to operate as a standalone power source in conjunction with a DC prime mover. The multi-phase machine can operate with one three phase capacitor bank which does not lead to complete shutdown of the system during fault conditions across one of its two sets of its stator windings. In the analysis the machine is connected to different capacitor configuration and the influence of these connections on the machine performance during no load and load have been implemented. Experimental results include voltage build up of the machine with different excitation capacitors at both sets of stator windings with changing speed during no load condition, resistive load condition and resistive inductive load condition with simple shunt and short shunt configuration.